2022
DOI: 10.1111/jfb.15155
|View full text |Cite
|
Sign up to set email alerts
|

New records of rare deep‐sea fishes (Teleostei) collected from off north‐eastern Brazil, including seamounts and islands of the Fernando de Noronha Ridge

Abstract: Here we report on new data on the occurrence and distribution of rare deep‐sea fishes (Teleostei) collected from off north‐eastern Brazil, including seamounts and oceanic islands of the Fernando de Noronha Ridge (Rocas Atoll and Fernando de Noronha Archipelago). Collections were made by the French RV Antea during the ABRACOS (Acoustics along the BRAzilian COaSt) expeditions between 29 September and 21 October 2015, and 9 April and 10 May 2017. Occurrences of Photostylus pycnopterus (Alepocephalidae), Gigantura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The ABRACOS expeditions have been contributing by providing new information on the composition and ecology of mesopelagic fishes in the western tropical Atlantic (e.g., Afonso et al, 2021;Eduardo et al, 2018Eduardo et al, , 2019Eduardo et al, , 2020aEduardo et al, , 2020bMincarone et al, 2019Mincarone et al, , 2020Mincarone et al, , 2021Mincarone et al, , 2022Villarins et al, 2022). Recently, Villarins et al (2022) reported the occurrence of 55 species of stomiiforms off northeastern Brazil, including some new records in Brazilian waters and in the western South Atlantic.…”
Section: Discussionmentioning
confidence: 99%
“…The ABRACOS expeditions have been contributing by providing new information on the composition and ecology of mesopelagic fishes in the western tropical Atlantic (e.g., Afonso et al, 2021;Eduardo et al, 2018Eduardo et al, , 2019Eduardo et al, , 2020aEduardo et al, , 2020bMincarone et al, 2019Mincarone et al, , 2020Mincarone et al, , 2021Mincarone et al, , 2022Villarins et al, 2022). Recently, Villarins et al (2022) reported the occurrence of 55 species of stomiiforms off northeastern Brazil, including some new records in Brazilian waters and in the western South Atlantic.…”
Section: Discussionmentioning
confidence: 99%
“…The high number of new records made during the ABRACOS expeditions reflects not only the high diversity of the SWTA, but also the overall lack of scientific information on deep-sea diversity in the region, as noted previously (e.g., Reis et al, 2016;Mincarone et al, 2022). The United Nations Decade of Ocean Science roadmap recognizes the deep-sea as a frontier of science and discovery (Ryabinin et al, 2019).…”
Section: Role Of International Cooperation For the Decade Of Deep Oce...mentioning
confidence: 91%
“…Platyberyx pietschi, in turn, was known from just two specimens collected in the western Central Atlantic, one specimen collected in the central Pacific, and another from the western South Pacific (Stevenson and Kenaley, 2013;Mincarone et al, 2019). Other species considered rare worldwide that were collected in the ABRACOS expeditions are Aulotrachichthys argyrophanus, Rhynchohyalus natalensis, Eumecichthys fiski, Macrouroides inflaticeps, Pseudoscopelus cordilluminatus, Melamphaes leprus, and Gigantactis watermani (Pimentel et al, 2020;Afonso et al, 2021;Mincarone et al, 2021b;Mincarone et al, 2022).…”
Section: Notable Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trying to identify differences between closely related organisms, with the goal of describing species, can be even more difficult when specimens of those species are hard to access, or from underexplored regions of the globe. Nowhere is this more true than in the deep-sea, where new records are continually being made (Bañ on et al, 2020;Mincarone et al, 2022Mincarone et al, , 2014. Not only is a huge amount of the deep sea underexplored, with visual evidence of organisms sparce, but when samples are retrieved from the deep sea they can be prone to taxonomic confusion and have poor diagnostic features (Teramura et al, 2021).…”
mentioning
confidence: 99%